Factors Associated with Exclusive Breast Feeding Practices among Mothers of Infant and Young Children in a Primary Health Care Centre, Kathmandu: A Cross-Sectional Study - Paudel, Narayani; Parajuli, Puspa (Birat Journal of Health Sciences, 2018)
Introduction: Exclusive breast feeding up to first six months of life is the safest and healthiest practice for children all over the world. Various factors may affect to the exclusive breast-feeding though it is necessary for promotion of child's health. Objective: The objective of this study was to identify the factors associated with exclusive breast feeding practices among mothers of infant and young children. Methodology: A cross-sectional study was carried out at Gokarna Primary Health Care Centre, Kathmandu. Total 137 mothers having at least one child 0-23 months of age, attending to Maternal and Child Health Clinic were purposively selected for the study. Consecutive sampling was done. All the mothers who meet the criteria during the period of data collection (August to September, 2017) were included in the study. Ethical clearance was obtained from the Institutional Review Committee of Kathmandu Medical College, Kathmandu. Written consent was taken from each respondent and face to face interview technique was used to collect the data using pre-designed structured questionnaire. Data were analyzed using Statistical Package for Social Science 16.0 version. Both descriptive and inferential statistics were used for data analysis. Results: Majority of the respondents (56.9%) had adequate knowledge on exclusive breast feeding, about 54% of the mothers had initiated breast feeding within one hour of delivery and all in all mothers had ever breast fed their child. More than one third (36.5%) of babies were given pre-lacteal fed, around two thirds of babies were breast fed exclusively at least less than one month but only around 40% of the babies had received exclusive breast feeding for six months. Exclusive breast feeding was significantly associated with, normal vaginal delivery, pre-lacteal fed given and having adequate level of knowledge regarding exclusive breast feeding Conclusion: On the basis of findings, mode of delivery, pre-lacteal feeding and level of knowledge on exclusive breast feeding were the factors significantly associated with exclusive breast feeding. The practice of exclusive breast feeding for six months of age was not up to the mark. BJHS 2018;3(2)6:413-417.